A COMPREHENSIVE OVERVIEW OF HINDU WOMEN'S RIGHT IN PROPERTY:AN OVERVIEW - Dayma, Dinesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
“It is not easy to eradicate deep seated cultural values or to alter traditions that perpetuate discrimination. It is fashionable to denigrate the role of law reform in bringing about social change. Obviously law, by itself, may not be enough. Law is only an instrument. It must be effectively used. And this effective use depends as much on a supportive judiciary as on the social will to change. An active social reform movement, if accompanied by legal reform, properly enforced, can transform society.” Hon’ble Justice Sujata V. Manohar